Topology and application of bidirectional isolated dc-dc converters - Tan N.M.L.; Abe T.; Akagi H. (2023)
A bidirectional isolated dc-dc converter manages the power flow between an energy storage device and a dc bus with functions of galvanic isolation and voltage matching. Research and development of these converters focus on improving efficiency and power density. This paper presents and compares various configurations of bidirectional isolated dc-dc converters. It also illustrates the performance of a 6-kW, full-bridge, bidirectional isolated dc-dc converter operating at 4 kHz, which is suitable for output power leveling of photovoltaic generation systems connected to homes and office buildings. The maximum efficiency of the dc-dc converter is measured at 98.1% during battery charging and at 98.2% during battery discharging. The converter maintains a high efficiency of more than 97% for a wide range of power transfer. 2011 IEEE.